Do Children Classified With Specific Language Impairment Have a Learning Disability in Writing? A Meta-Analysis. (July 2020) - Graham, Steve; Hebert, Michael; Fishman, Evan; Ray, Amber B.; Rouse, Amy Gillespie
In this meta-analysis, we examined whether children classified with specific language impairment (SLI) experience difficulties with writing. We included studies comparing children with SLI to (a) typically developing peers matched on age ( k = 39 studies) and (b) typically developing younger peers with similar language capabilities ( k = six studies). Children classified with SLI scored lower on writing measures than their typically developing peers matched on age ( g = −0.97) when all writing scores in a study were included in the analysis. This same pattern occurred for specific measures of writing: quality ( g = −0.92), output ( g = −1.00), grammar ( g = −0.68), vocabulary ( g = −0.68), and spelling ( g = −1.17). A moderator analysis revealed that differences in the writing scores of children classified with SLI and typically developing peers matched on age were not as large, but were still statistically significant, when assessment involved a contrived response format (vs. measured based on students' writing), researcher-created measures (vs. norm-referenced tests), or SLI included just children with a speech disorder (vs. children with a language disorder). Children classified with SLI further scored lower on writing than typically developing peers with similar language capabilities ( g = −0.47). We concluded that children with SLI experience difficulties with writing.